Operational Mechanisms and Collaborative Optimization Paths of Industry-Education Integration Service Organizations in the Guangdong-Hong Kong-Macao Greater Bay Area - Liu, Hongyu; Wu, Dajian (Asia Pacific Economic and Management Review, 2025)
In the context of high-quality development in the Guangdong-Hong Kong-Macao Greater Bay Area, industry-education integration service organizations serve as institutional hubs connecting the educational system with the industrial sector. These organizations play an increasingly critical role in optimizing regional education structures and facilitating the transformation of technological achievements. Drawing on multi-actor collaborative governance theory, this study constructs a four-dimensional analytical framework—platform functionality, collaborative mechanism, resource integration, and institutional embedding—and employs empirical testing using structural equation modeling (SEM) based on survey data to systematically examine the operational logic and performance mechanisms of service organizations. The findings reveal persistent challenges including goal divergence, communication inefficiencies, resource fragmentation, and institutional lag. Among the four factors, the collaborative mechanism has a significant positive impact on organizational performance, and government support, school-enterprise cooperation, and resource integration efficiency are identified as key pathways. Accordingly, this paper offers policy recommendations focused on institutional alignment, enterprise incentives, platform governance, and performance evaluation, aiming to provide both theoretical foundations and practical solutions for advancing regional education-industry integration.